PENGARUH FREKUENSI PEMBERIAN PAKLOBUTRAZOL DAN DOSIS PUPUK NPK 16-16-16 DALAM MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Firda Rohatul Widad; Agus Sulistyono; Djarwatiningsih Djarwatiningsih (UPN VETERAN JAWA TIMUR, 2021)
Cayenne pepper (Capsicum frutescens L.) is one of the plants favored by the people of Indonesia. The production of cayenne pepper has increased but has not been able to meet the national demand for cayenne pepper, so the government still has to import it. This research aims to determine the effect of frequency of paclobutrazol and dose of NPK fertilizer on the growth and yield of cayenne pepper. The research was conducted in Gresik on November 2020 to March 2021.This research is a factorial experiment based on a Split Plot (RPT) consisting of 2 factors. The first factor is frequency of paclobutrazol (P) and second factor is dose of NPK fertilizer (N) and was repead 3 times. The combination between the frequency of paclobutrazol and dose of NPK fertilizer gave a significant effect on all parameters except the flowering age and fruit maturity. The combination of treatment without the application of paclobutrazol + 24 g/plant NPK 16-16-16 increased plant height by 18% and leaf number by 48% compared to control. The best result is combination of 2 times application of paclobutrazol + 24 g/plant on parameters number of flowers, fruitset, total number of fruits per plant, and total fruit weight per plant. The best results at the NPK dose of 24 g/plant were able to accelerate the flowering age (43.79) day and fruit maturity (86.04) day.